Circumstances Probing Internet Banking Users to Use Alternative Channels: Thematic Matrix Display Analysis - Adapa, Sujana (Information Management and Business Review, 2013)
This study highlights the circumstances that actually probe internet banking users to switch to the use of alternative channels in performing their banking transactions within Australian context. Data obtained from 372 internet banking users was analysed by employing thematic matrix analysis technique to identify various macro and micro thematic categories in that hierarchical order of importance. Results revealed factors such as ‘unable to perform over the internet’, ‘lack of internet access’, ‘not sure of something’, ‘problem rectification’, ‘proximity to auxiliary facilities’ and ‘type of internet connectivity’ were relevant in identifying the circumstances under which they preferred to use other banking channels. The study provides important implications for the formulation of effective service delivery channel management strategies by way of implementing effective mechanisms. Moreover, the study also outlines important guidelines for practical solutions in order to reduce the impact of situational barriers thus focusing on effective customer retention strategies. With the information provided by this research, bank executives, consultants and academics will have enhanced knowledge of the service areas they need to focus on to improve customer satisfaction, retention and profitability in the financial services businesses.